Colony Structure and Nest Location of Two Species of Dacetine Ants: Pyramica ohioensis (Kennedy & Schramm) and Pyramica rostrata (Emery) in Maryland (Hymenoptera: Formicidae) - Richard M. Duffield (Psyche: A Journal of Entomology, 2011)
The discovery of numerous Pyramica ohioensis and P. rostrata colonies living in acorns, as well as the efficient recovery of colonies from artificial nests placed in suitable habitats, opens a new stage in the study of North American dacetine ants. Here we present detailed information, based on 42 nest collections, on the colony structure of these two species. P. ohioensis colonies are smaller than those of P. rostrata. Both species are polygynous, but nests of P. ohioensis contain fewer dealate queens than those of P. rostrata. This is the first report of multiple collections of Pyramica colonies nesting in fallen acorns, and of the use of artificial nesting cavities to sample for dacetines in the soil and leaf litter. We describe an artificial cavity nest design that may prove useful in future investigations.